2012
DOI: 10.1158/1078-0432.ccr-11-3130
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Myeloma Effects of the Novel Anthracycline Derivative INNO-206

Abstract: Purpose: Doxorubicin has shown efficacy especially in combination treatment for the treatment of multiple myeloma; however, its side effects limit its use. INNO-206 is an albumin-binding prodrug of doxorubicin, which is released from albumin under acidic conditions. Because INNO-206 has not been previously evaluated in any hematologic malignancy, we determined its anti-multiple myeloma effects.Experimental Design: The anti-multiple myeloma effect of at different pH levels on multiple myeloma cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Further in vivo anti‐multiple myeloma effects and toxicity of 31 on mice with LAGκ induced tumour showed that a weekly dose of 10.8 mg/kg via intravenous administration (equivalent to 8.0 mg/kg of free doxorubicin) reduced extensively the tumour volumes between days 28 and 42 ( P =0.0152 to P =0.0036), whereas equivalent and lower doses of doxorubicin led to significant toxicity, resulting in the death of all animals by day 42 . This is consistent with previous reports about the diminished cardiotoxicity and mitochondrial impairments of derivative 31 , and consequent two‐ to fivefold higher lethal concentration as compared to doxorubicin .…”
Section: Anthracyclinessupporting
confidence: 89%
See 2 more Smart Citations
“…Further in vivo anti‐multiple myeloma effects and toxicity of 31 on mice with LAGκ induced tumour showed that a weekly dose of 10.8 mg/kg via intravenous administration (equivalent to 8.0 mg/kg of free doxorubicin) reduced extensively the tumour volumes between days 28 and 42 ( P =0.0152 to P =0.0036), whereas equivalent and lower doses of doxorubicin led to significant toxicity, resulting in the death of all animals by day 42 . This is consistent with previous reports about the diminished cardiotoxicity and mitochondrial impairments of derivative 31 , and consequent two‐ to fivefold higher lethal concentration as compared to doxorubicin .…”
Section: Anthracyclinessupporting
confidence: 89%
“…In U266 cells, the acidic environment (pH 5) also increased the anti‐proliferative effect of 31 , but it was detrimental to the activity of free doxorubicin at all concentrations investigated, compared to results under physiological conditions tested at pH 7. Based on a chorioallantoic membrane/feather bud (CAM/FB) model, the antiangiogenic effects of 31 were also pH‐dependent, in agreement with early findings for anthracyclines, which showed inhibition of blood vessel formation due to reduced hypoxia‐inducible factor (HIF‐1) level in tumour cells …”
Section: Anthracyclinessupporting
confidence: 84%
See 1 more Smart Citation
“…The on-going clinical studies suggest that INNO-206 can be administered safely at higher doses in patients than free doxorubicin, resulting in better efficacy compared with the currently available anthracyclines to treat several types of cancer. 188,190,191 …”
Section: Medical Applications Based On Hsa-conjugates or Hsa-bindimentioning
confidence: 99%
“…In addition to DOX, HSA is able to bind its prodrugs (6-maleimidocaproyl)hydrazone (INNO-206, DOXO-EMCH), which exhibits better efficacy than DOX in numerous cancer models [35, 48, 49, 66, 67]. In a recent study of human pancreatic cancer cells, MIA PaCa-2, treated with the combinations of DOX and HSA-DOXO-EMCH, a 1:5 ratio of DOX to HSA-DOXO-EMCH has shown the highest synergistic profile in the cytotoxicity assay when DOX is introduced 6 hours prior to the addition of HSA-DOXO-EMCH [49].…”
Section: Small Molecule Therapeuticsmentioning
confidence: 99%